Oxidized LDL‐Exposed Human Macrophages Display Increased MMP‐9 Expression and Secretion Mediated by Endoplasmic Reticulum Stress. Issue 4 (28th November 2016) - Sanda, Gabriela M.; Deleanu, Mariana; Toma, Laura; Stancu, Camelia S.; Simionescu, Maya; Sima, Anca V.
ABSTRACT: Oxidatively modified low‐density lipoproteins (oxLDL) alter the proper function of the endoplasmic reticulum (ER), inducing ER stress (ERS), which consequently activates inflammatory pathways in macrophages. Matrix metalloproteinase‐9 (MMP‐9) is the main protease acting on the degradation of the extracellular matrix and the ensuing destabilization of the atherosclerotic plaque. We aimed to investigate whether ERS induced by oxLDL or tunicamycin (TM) in human macrophages is associated with the stimulation of MMP‐9 expression and secretion. The results showed that oxLDL induced in THP‐1 macrophages: (i) increase of MMP‐9 gene expression and its pro‐form secretion, (ii) intracellular accumulation of 7‐ketocholesterol, (iii) ERS activation (increased eIF2α phosphorylation, XBP1 and CHOP mRNA levels, and Grp78 protein expression), and (iv) oxidative stress (increased levels of reactive oxygen species and NADPH oxidase activity). Incubation of macrophages with ERS inducer, TM determined the secretion of both pro‐ and active‐form of MMP‐9 and oxidative stress. Treatment of oxLDL or TM‐incubated cells with ERS inhibitor, sodium phenylbutyrate decreased MMP‐9 gene expression, secretion, and activity. The inhibitor of NADPH oxidase, apocynin, decreased XBP‐1 and CHOP mRNA levels, and MMP‐9 gene expression and secretion in oxLDL‐exposed cells. In conclusion, oxLDL stimulate MMP‐9 expression and secretion in human macrophages by mechanisms involving ERS. J. Cell. Biochem. 118: 661–669, 2017. © 2016 Wiley Periodicals, Inc. Abstract : OxLDL‐induced ERS is involved in MMP‐9 gene expression up‐regulation and secretion in macrophages. OxLDL induce 7‐ketocholesterol accumulation in macrophages.